Clinical outcomes of efficacy in food allergen immunotherapy trials. Issue 3 (29th June 2023) - Bartha, Irene; Rodríguez Del Río, Pablo
Abstract : Purpose of review: With food allergy affecting millions of children worldwide, the consolidation of food allergen immunotherapy represents an encouraging therapeutic option, that might expand in the next few years to reach greater number of candidates. This review aims at providing a critical overview of the efficacy outcomes employed in food allergen immunotherapy trials (AIT). Recent findings: Understanding efficacy endpoints rely on identifying what and how these are being measured. Desensitization, as the efficacy of the therapy to increase the patient's reactivity threshold to the food during therapy, and Sustained Unresponsiveness, withholding such efficacy even if the therapy is withdrawn, are nowadays considered the main parameters of efficacy evaluation. Quality of life is a promising variable to capture food AIT impact from the patient's perspective. There is a relevant degree of heterogeneity across studies in outcomes definitions and also in oral food challenges design, the tool that is more spread to assess results, hampering study comparison. Summary: Interpreting the results of a clinical trial, and comparing data from different studies is an important task, both for the researcher and the clinician, that should be done after a careful analysis of the outcomes and the evaluation tools used.